De bois e outros bichos: nuances do novo Realismo brasileiro - Tânia Pellegrini (Estudos de Literatura Brasileira Contemporânea, 2012)
The article analyses two short stories by Marçal Aquino, “Boi” and “A exata distância da vulva ao coração”, which were published in two different selections. It tries to verify how Realism represents in them the stressed relations between the social and the fictional. Revisiting traditional genres like Tragedy and Melodrama, in a way that accommodates them to the commercial requirements of the Cultural Industry, Aquino explores the subject of Brazilian urban violence, in its symbolic and concrete manifestations.